Real‐world outcomes of patients with locally advanced or metastatic epithelioid sarcoma. Issue 8 (9th December 2020) - Gounder, Mrinal M.; Merriam, Priscilla; Ratan, Ravin; Patel, Shreyaskumar R.; Chugh, Rashmi; Villalobos, Victor M.; Thornton, Mark; Van Tine, Brian A.; Abdelhamid, Amr H.; Whalen, Jennifer; Yang, Jay; Rajarethinam, Anand; et al.
Abstract : Background: Limited data are available on the real‐world effectiveness and safety of systemic therapies for advanced (surgically unresectable and/or metastatic) epithelioid sarcoma (ES). Methods: A retrospective medical records review was conducted in patients with advanced ES who were initiating first‐line or ≥2 lines of systemic therapy (2000‐2017) at 5 US cancer centers. The real‐world overall response rate (rwORR), the duration of response (rwDOR), the disease control rate (rwDCR) (defined as stable disease for ≥32 weeks or any duration of response), and progression‐free survival (rwPFS) were assessed by radiology reports. Overall survival (OS), rwDOR, and rwPFS were estimated from the time therapy was initiated using the Kaplan‐Meier method. Serious adverse events were assessed. Results: Of 74 patients (median age at diagnosis, 33 years; range, 10.6‐76.3 years), 72% were male, and 85% had metastatic disease. The median number of lines of therapy was 2 (range, 1‐7 lines of therapy), and 46 patients (62%) received ≥2 lines of systemic therapy. First‐line regimens were usually anthracycline‐based (54%) or gemcitabine‐based (24%). For patients receiving first‐line systemic therapy, the rwORR was 15%, the rwDCR was 20%, the median rwDOR was 3.3 months (95% CI, 2.1‐5.2 months), the median rwPFS was 2.5 months (95% CI, 1.7, 6.9 months), and the median OS was 15.2 months (95% CI, 11.4‐21.7 months). For those who received ≥2 lines of systemic therapy, the rwORR was 9%, the rwDCR was 20%, the median rwDOR was 4.5 months (95% CI, 0.7‐5.6 months), and the median rwPFS was 6.0 months (95% CI, 3.2‐7.4 months). Over one‐half of patients (51.4%) experienced an adverse event, most frequently febrile neutropenia (14%), pain (10%), anemia, dyspnea, fever, thrombocytopenia, or transaminitis (5% each). Conclusions: Systemic therapies demonstrate limited efficacy in patients with advanced ES and have associated toxicities. Abstract : This retrospective medical records review of patients with advanced epithelioid sarcoma receiving first‐line or ≥2 lines of systemic therapies indicates that cytotoxic chemotherapies have limited efficacy, and more than one‐half of patients experience adverse events. The results highlight the unmet medical need in patients with this ultrarare and aggressive subtype of soft tissue sarcoma.